(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the effect of designing a computer program with interactive multimedia technology to improve achievement for students of the Department of Life Sciences in the computer course test. To achieve this, the researcher put the following zero hypotheses:- There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group who study using the computer program prepared with interactive multimedia technology and the average scores of the students of the control group who study in the usual way in the overall post achievement test.